TINGKAT STRESS CAREGIVER ANAK BERKEBUTUHAN KHUSUS: A LITERATUR REVIEW - Keysha Bilbina Putri Zaenal; Furkon Nurhakim; Kurniawan (Jurnal Keperawatan Malang, 2026)
Background: Caregivers of children with special needs are at risk of experiencing psychological stress due to complex and long-term caregiving demands. Intensive care requirements and environmental factors may increase caregiver burden.Purpose: This study was conducted to identify and understand the extent of stress experienced by caregivers of special needs children.Methods: This study employed a literature review design using the PCC (Population, Concept, Context) approach. Articles were retrieved from PubMed, Scopus, EBSCO, and ScienceDirect using predefined keywords. Inclusion criteria were articles published between 2020–2025, written in Indonesian or English, and available in full text. The selection process followed PRISMA guidelines, resulting in 9 eligible articles. Data were analyzed descriptively.Results: The findings indicate that caregivers of children with special needs tend to experience moderate to high stress levels. Contributing factors include child-related conditions (behavioral problems and limited independence) and caregiver-related factors such as low social support and ineffective coping strategies. Caregiving burden and limited personal time also contribute to increased stress.Implications: These findings highlight the importance of caregiver-focused interventions in managing stress. The results can serve as a basis for developing nursing interventions and future research on caregiver stress management. Keywords: Caregiver; Children with special needs; Stress Levels